EVALUATION AVAILABILITY OF NARCOTICS AND PSYCHOTROPICS IN PHARMACY IN MEDAN CITY REGION - Susanti, Julia; Reveny, Julia; Wiryanto, Wiryanto (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Materials and Methods: This research use descriptive method using questionnaire instrument to 85 pharmacists in charge of pharmacy (APA) and 85 owners of pharmacy capital (PMA), then data are processed using SPPS windows. Results: The results of the questionnaire on the answers of respondents APA and PMA showed pharmacies that provide drugs class of narcotics and psychotropic in Medan 67 (43.51%), which provides narcotics only 2 (1.30%), which provides psychotropic drugs only 21 (13.64%) and pharmacies that do not provide drugs class of narcotics and psychotropic 64 (41.56%). The most common reason for narcotics and psychotropic drugs is the demand for prescription drugs at pharmacies 38 (86.36%), whereas the most reason for not providing narcotics and psychotropic drugs is that there are no or very few prescriptions of narcotics and psychopathic drugs that go into pharmacies 31 (75.61%). Conclusion: While reporting the result that reported drug with narcotic program online (SIPNAP) 46 (29.87%) with the reason most because not understand how to make and send report SIPNAP 41 (85.42%).